Ag(I)/Au(I)-Catalyzed Domino Propargylation/Aza-Annulation to Access Coumarino[4,3-b]pyridines - Reddy, Chada Raji; Edhara, Venkatareddy; Kumari, Ankita; Vijender, Adla (Synthesis, 2025)
An approach for the synthesis of diversely substituted coumarino[4,3-b]pyridines (5H-[1]benzopyrano[4,3-b]pyridin-5-ones), involving the annulation of 4-aminocoumarins with propargylic alcohols, is reported. The reaction proceeds through C-3 propargylation followed by an aza-annulation in a domino manner in the presence of AgSbF6/AuCl(PPh3) as the catalytic system. The products can be synthesized from a broad range of propargylic alcohols, demonstrating the compatibility with different functional groups.
Keywords: coumarino[4,3-b]pyridine; 5H-[1]benzopyrano[4,3-b]pyridin-5-one; propargylic alcohol; propargylation; aza-annulation; domino reaction